Development of educational environment of secondary school in conditions of the integration into the european education space - Ivanytska Olga; Red'ko Sergey (Borys Grinchenko Kyiv Metropolitan University, 2016)
The article analyzes the development priorities of the educational environment of secondary education schools in Ukraine as the basis of integration into the European educational space. The article lists priority tasks of modern Ukrainian secondary education, which execution will contribute to the successful integration into the European educational space. Directions of the state policy Ukraine on development of secondary education in accordance with the law was considered. It is need to promote the development of multiculturalism in general secondary education, which helps prepare modern youthto intercultural cooperation and communication with different cultures, religions, nationalities in terms of integration into the global educational space. However, this process requires improvement of regulatory support and development practical recommendations for its implementation. In the multicultural society to Ukraine appearsthe task before modern school of preparation of young people for cooperation and intercultural communication with people of different cultures, religions, nationalities. The condition of a continuous process of purposeful socialization of individualin the modern globalized world became multicultural education. It was determined that one of the directions of realization of polycultural education as a continuous process of purposeful socialization of individual in the European is the implementation of bilingual learning in institutions of secondary education in Ukraine. The results of carried out experiment regarding the introduction the bilingual learning, which confirmed the hypothesis that bilingual learning contributes not only to improve the overall students' language competence, but also increases the level of educational achievements.